Microstructure and Mechanical Properties of Metals Subjected to Equal Channel Angular Pressing (ECAP) Process - M. A. H., Abu Hassan; Dayangku Noorfazidah, Awang Shri (2017)
Equal Channel Angular Pressing (ECAP) is one of the most efficient technique in metal forming process which induced severe plastic deformation (SPD) for the production of bulk ultrafine-grained metals. This research used Titanium CP Grade 2 and Aluminum Alloy 6061 to investigate the microstructure and mechanical properties of both materials after ECAP process. The materials were extruded through die channel angle of 126º internal and 10º external under pressure of 60 bar. The result shows that there is significant increase in grain refinement and hardness after ECAP process for both of the materials.